Measurement of Stress Among Doctors in Intensive Care Unit (ICU) (Medical Forum Monthly, 2024)
Objective: The objectives of the study were to identify stressors and to measure their magnitude of stress on doctors of ICU and to identify major stressors and major distress working in ICU.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Intensive Care Units (ICUs) of four hospitals of Lahore namely Doctors Hospital, Ittefaq Hospital Trust, Jinnah Hospital Lahore General Hospital Lahore for one month, during spring 2016.Materials and Methods: It was in which 40 doctors working in intensive care units participated. The collected data through questionnaire was analyzed by using SPSS 16.0. Frequencies and percentages were calculated and data was presented in tables and diagrams. Confidentiality of the information was also ensured.Results: Among 40 doctors, 47.5% were up to 30 years old and 72.5% were males. 22.5% strongly disagreed that their job has very little chances of promotion. 37.5% doctors agreed somewhat that their workload is too heavy. 35.0% agreed that they seldom receive adequate acknowledge or appreciation when their work is really good. 37.5% doctors agreed somewhat that they often receive threats from patient attendants. 37.5% strongly disagreed that their workplace environment is not pleasant. 35.0% doctors agreed somewhat that they tend to have frequent arguments with seniors, coworkers or patients/attendants. 40.0% disagreed that they often feel their job to be boring. 25.0% doctors agreed while 17.5% strongly agreed that they have sense of un-achievement when results of treatment are not good despite of hardworking on patient's treatment. 62.5% doctors had average stress.Conclusion: Majority of doctors were dissatisfied with the chance of promotion and heavy workload. Threat from patients’ attendants was the leading cause of stress observed among majority of the ICU doctors. Sense of un-achievement was also the important cause of stress despite of hardworking on patient’s treatment.